Synergistic Stabilization of Potassium Metal Anodes Through Orange-Peel Elimination and Robust Solid-Electrolyte Interphase Formation. - He,P; Han,Y; Zhou,Y; He,R; Xu,R; Zhao,Y; Wang,J; Ren,W; Hopper,M; An,Q; Makarov,D; Gilmore,IS; et al. (Adv Sci (Weinh), 2026)
Potassium (K) metal anodes are attractive for next-generation rechargeable batteries due to their low redox potential and elemental abundance, yet their practical application is hindered by dendrite growth and unstable solid-electrolyte interphases (SEIs). Here, we replace conventional roll pressing with a cutting-based fabrication strategy to produce crystallographically more uniform and minimally deformed K surfaces, while independently tuning SEI chemistry through electrolyte concentration. This approach establishes a unified framework that elucidates the synergistic coupling between surface uniformity and SEI robustness in governing K plating/stripping stability. Only their synergy delivers fast kinetics, high areal capacity, and long-term reversibility. Consequently, optimized K||K symmetric cells operate stably for over 4 000 h at 0.5 mA cm-2 and 4 mA h cm-2. Full cells paired with K1.97Mn[Fe(CN)6] cathodes retain 90% capacity after 1200 cycles. These findings highlight the importance of concurrent morphological and interfacial regulation for practical K metal anodes.